1991
DOI: 10.1104/pp.96.2.349
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence for Symplastic Phloem Loading

Abstract: Experimental protocols used to study the route(s) of phloem loading in source leaves are evaluated; they include the analysis of plasmodesmatal ultrastructure and distribution, mobile compounds in the free space, loading patterns of exogenous sugars, the site of sugar synthesis, and dye coupling. All these methods have drawbacks. There are indications that some plants, espe-cially those that translocate the raffinose series of sugars, load by a symplastic (through plasmodesmata) pathway, but the evidence is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…However, downregulation of SUT1 did not appreciably modify the V. phoeniceum vein images, except in the most severely downregulated line, and then not consistently. These results are similar to those in which sucrose transporter activity in RFO-transporting plants is inhibited with PCMBS (19). Apparently, when sucrose transporter activity is blocked, [ 14 C]sucrose enters the tissue by the non-saturable, PCMBSinsensitive uptake mechanism (36,37) and is then sequestered in the veins by diffusion through plasmodesmata and polymer trapping in the intermediary cells (34).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, downregulation of SUT1 did not appreciably modify the V. phoeniceum vein images, except in the most severely downregulated line, and then not consistently. These results are similar to those in which sucrose transporter activity in RFO-transporting plants is inhibited with PCMBS (19). Apparently, when sucrose transporter activity is blocked, [ 14 C]sucrose enters the tissue by the non-saturable, PCMBSinsensitive uptake mechanism (36,37) and is then sequestered in the veins by diffusion through plasmodesmata and polymer trapping in the intermediary cells (34).…”
Section: Discussionsupporting
confidence: 77%
“…A ''polymer trap'' mechanism (18)(19)(20) has been proposed to explain how sucrose is loaded through plasmodesmata in RFO plants. According to this model, sucrose diffuses through plasmodesmata from mesophyll cells to intermediary cells, where it is converted into RFOs.…”
mentioning
confidence: 99%
“…Physiological studies have indicated that an apoplastic loading step may not be required for delivery of assimilates to the phloem of stachyose-translocating plants (8,17,19,20). The present models, therefore, conjecture that synthesis of the raffinose oligosaccharides may take place within the intermediary cells from mesophyll-derived galactinol and sucrose.…”
Section: Introductionmentioning
confidence: 69%
“…The present models, therefore, conjecture that synthesis of the raffinose oligosaccharides may take place within the intermediary cells from mesophyll-derived galactinol and sucrose. These precursors are thought to be delivered to the intermediary cells via the abundant plasmodesmata that interconnect these cells and the mesophyll (19,20). If these models prove to be correct, then an additional spatial component will have been added to the carbon-partitioning story that probably does not exist for sucrose-translocating species.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological and physiological evidence obtained for cucurbit leaves now indicates that stachyose may be synthesized within the minor vein phloem from mesophyll-derived precursors (5). Current structural and physiological evidence also suggests that the delivery of these precursors may follow a symplastic pathway (5,15,18,19). In cucurbits, therefore, the effects of chilling on carbon partitioning within leaf tissues may be even more complex than is currently understood for sucrose-translocating species, in light of the importance of calcium balance in the control of solute movement through plasmodesmata (14).…”
mentioning
confidence: 99%